UPAYA PENINGKATAN PRODUKTIVITAS LAHAN DENGAN SISTEM BUDIDAYA LORONG DAN PEMBERIAN KAPUR DOLOMIT DI KABUPATEN CIREBON, JAWA BARAT - Daru Mulyono (Jurnal Rekayasa Lingkungan)
The objective of the research is to know the effect of Alley Cropping to the land fertility, especially with the treatment of organic matter and combination between organic matter and dolomit, with regard to soybean production. The research used Complete Randomized Design with One Way Analysis of Variance, Regression, and Correlation in order to know the effect of treatment to the land fertility. The research was carried out in Cirebon Regency, West Java Province, during three planting seasons from 2007 to 2008. The results of the research showed that Flemengia congesta as a fence crop or hedgerows was signifi cant to land fertility through improvement of nutrients availability, increasing pH, decreasing availability of aluminium (Al). The effect of organic matter from prunning of the hedgerows into the soil to a high of 5,0 ton/ha will increase average soybean production from 13.974 kw/ha (dry grain) to 18.176 kw/ha or increase 30,07 %, whereas the effect of organic matter 5,0 ton/ha combined with dolomit 2,5 ton/ha will increase average soybean production from 13.974 kw/ha to 19.983 kw/ha or increase 43.00 %. The effect of organic matter 10,0 ton/ha combined with dolomit 2,5 ton/ha will increase average soybean production from 13.974 kw/ha to 21.966 kw/ha or increase 57.19 %.